EFFECT OF INTAKE CONDITIONS ON HEAT TRANSFER CHARACTERISTICS FOR THE HYDROGEN FUELED ENGINE - R., Bharathikannan (International Journal of Psychosocial Rehabilitation, 2017)
In this work, effect of the inlet conditions for the intake charge on the in-cylinder heat transfer characteristics for port injection Hydrogen Fueled Engine H2ICE are investigated through steady state simulation. One-dimensional gas dynamics was used to describe the flow and heat transfer in the components of the engine model. Firstly a brief demonstration for the model description was inserted; followed by the model governing equations. The engine model is simulated with variable engine speed and AFR with influence of the variation of intake charge conditions (pressure and temperature). Engine speed varied from 2000 rpm to 5000 rpm with increments equal to 1000 rpm, while AFR changed from stoichiometric to lean limit. The inlet pressure is varied from 0.95 bar to 1.05 bar with 0.05 interval and the inlet temperature varied from 290 to 310 with 10 interval. The combined effects for the intake charge conditions with variation of AFR and the engine speed on the in-cylinder heat transfer characteristics for port injection H2ICE are presented in this paper. The baseline engine model is verified with existing previous published result. The results show that the heat transfer characteristics to be more affected by changes in the intake pressure than in the temperature. It is also found that the effect of change for the intake charge pressure disappeared for lean mixture. Beside that the acquired results are presented by examining the dependency of in-cylinder heat transfer rate on the engine speed and AFR.